Party change and electoral performance: assessing the impact of intraparty conflict on the Democrat and Hanura parties - Al-Hamdi, Ridho; Trianisa, Krisma; Kurniasari, Lenny; Lailam, Tanto; Nur Hayati, Neni; Mahmud, Ramli (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
This article examines the determining factors inducing the decreasing votes of two renowned political parties in Indonesia: The Democrat Party (PD) and the People Conscience Party (Hanura). As the ruling party in the 2009 election, the PD’s votes declined dramatically in the two following elections. Meanwhile, Hanura failed to exceed the parliamentary threshold in 2019. Methodologically, it is qualitative research by utilizing a comparative case approach. To gather data, this study employed in-depth interviews and documentary analysis and strengthened by NVivo 12plus platform by using Crosstab Query and Wordcloud Analysis to visualize data. By applying the party change indicators developed by Harmel and Janda, the findings revealed that leadership change was the most influential factor toward the poor performance of both parties in the electoral competition. Such leadership change caused a detrimental conflict and changed a dominant faction inside the party. More specifically, the corruption case behaved by the PD’s politicians aggravated the party charm, and the parliamentary threshold was a supporting aspect of the thrown out of Hanura from the parliament.